2019
DOI: 10.1128/aac.02526-18
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Identification of AbaR-Type Genomic Islands in Acinetobacter baumannii Reveals Diverse Insertion Sites and Clonal Lineage-Specific Antimicrobial Resistance Gene Profiles

Abstract: AbaR-type genomic islands (AbaRs) are important elements responsible for antimicrobial resistance in Acinetobacter baumannii. This study performed a large-scale identification of AbaRs to understand their distribution and compositions of antimicrobial resistance genes. We identified 2.89-kb left-end and 1.87-kb right-end conserved sequences (CSs) and developed a bioinformatics approach to identify AbaRs, using the CSs as signatures, in 3,148 publicly available genomes. AbaRs were prevalent in A. baumannii, bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 30 publications
3
45
1
Order By: Relevance
“…The comM gene product appears to play a role in integrating horizontally acquired DNA (Nero et al , ), but any advantage that the transposon may gain by inactivating this gene remains unclear. Tn6022‐related elements also account for the AbaR‐type genomic islands that are common in pathogenic Acinetobacter baumannii (Bi et al , ), although as indicated previously, relatives of this element are found broadly across bacteria and outside of clinical settings (Peters et al , ).…”
Section: There Are Numerous Families Of Tn7‐like Elements With Novel mentioning
confidence: 93%
“…The comM gene product appears to play a role in integrating horizontally acquired DNA (Nero et al , ), but any advantage that the transposon may gain by inactivating this gene remains unclear. Tn6022‐related elements also account for the AbaR‐type genomic islands that are common in pathogenic Acinetobacter baumannii (Bi et al , ), although as indicated previously, relatives of this element are found broadly across bacteria and outside of clinical settings (Peters et al , ).…”
Section: There Are Numerous Families Of Tn7‐like Elements With Novel mentioning
confidence: 93%
“…The sequencing of several A. baumannii genomes revealed a wide repertoire of antimicrobial resistance genes, many of which associated with transposable elements and insertion sequences and which might be found in genomic islands (GIs), known as AbaR (Zhu et al, 2013;Liu et al, 2014;Bi et al, 2019). Several AbaR islands have been described which can vary in size and are dynamically reshaped mainly due to the activity of transposases, recombinases and integrases (Krizova et al, 2011;Li et al, 2015;Hamidian and Hall, 2018;Bi et al, 2019). Resistance genes can also be found within plasmids, which can be exchanged intra-and interspecies (Leungtongkam et al, 2018;Wibberg et al, 2018) and even by prophages (Wachino et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Acinetobacter baumannii is responsible for healthcare-associated infections and concerns because of its intrinsic resistance to many antimicrobials and its ability to acquire resistance genes (1,2). A potential contributor to multi-drug resistance of A. baumannii is a genomic island, named AbaR, with a great diversity in gene content and carrying multiple putative antibiotic-resistance genes (3,4). The first report of AbaR described a large genomic island of 86 kbp in the epidemic A. baumannii strain AYE in 2006 (5).…”
Section: Introductionmentioning
confidence: 99%
“…The first report of AbaR described a large genomic island of 86 kbp in the epidemic A. baumannii strain AYE in 2006 (5). Since then, analysis of more than 3000 A. baumannii genomes deposited in the NCBI database revealed that AbaR are present in nearly 65% of them (4). With a transposon backbone, AbaR islands are considered as mobile genetic elements and present a modular structure (3,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation